Die Bevölkerungsverteilung in der Türkei 1965 und ihre Entwicklung seit 1935 - Louis, Herbert (ERDKUNDE, 1972)
Firstly the scale of the map and the choice of its general geographic elements are justified. Then the representation of the rural population by degrees of density (relative representation) its suitability for Turkey and the way it has been realized on the map are explained. In addition it is shown that the urban population of Turkey can well be figured by classes of the size of towns and cities and the way this has been carried out is demonstrated. Moreover it is demonstrated how the alterations in the distribution of rural and urban population between 1935 and 1965 have been indicated on the map. Following this the density of rural population and alterations of it since 1935 are discussed regionally. Regional differences depend on cultural diversity as well as on different natural conditions. In general the wetter marginal parts of Turkey, especially in the North and West, are better populated than the interior. Parts of the southern, south eastern and eastern border regions are very sparsely populated because of unfavourable natural conditions or for cultural reasons. Central Anatolia is settled sparsely but in relation with rainfall and temperature; basins of less than 1000 m altitude are the least populated while plateaus up to 1400 m have a little more population. Since 1935 many mountain regions and some areas around large cities have had low increase of rural population because of internal out-migration. But the least populated areas of the East and Southeast showed strong relative increase which, however, were low in absolute terms. Lastly the paper deals with the Turkish towns and cities. They show strong increase and are growing bigger. Up until now however a full system of big cities has only developed in the Northwest and West of the country with Istanbul, Izmir and Bursa and numerous smaller towns scattered at moderate distances. Ankara and Adana with their tributary towns are still rather isolated. Cities which are not really big but of more than moderate size represent centres for large parts of the country. But other wide regions have only more or less small towns as municipal centres. True industrial places are seldom found in Turkey.